Level of teaching pedagogical competences perceived by university students - Ruiz-Aquino, Mely (2020)
Objective. To Identify the level of pedagogical competencies of university teachers perceived by students of Universidad de Huánuco (UDH), 2020. Methods. It was a cross-sectional, observational and descriptive study. Population comprised 7853 students, with a sample of 350 students selected by probabilistic, random and strata sampling. The measurement instruments were a survey guide of demographic and academic characteristics of the sample, and a scale of the pedagogical competences of teachers, according to student’s perception. This last instrument was previously validated at a qualitative and quantitative level. For the inferential analysis, chi-square test was used for one sample. Results. According to university students, the level of pedagogical competences of university teachers were perceived in the majority (72.9%) at a low level. According to dimensions, 72.6% had low basic competences, 82.6% showed low specific competences and 85.4% indicated low transversal competences. On the other hand, there were statistically significant differences, depending on the level of pedagogical competences (high, moderate, low), with p <= 0.000. Conclusion. The level of pedagogical competences of university teachers according to the perception of students in a greater proportion is perceived at a low level.